Oil Palm Agroforestry Can Achieve Economic and Environmental Gains as Indicated by Multifunctional Land Equivalent Ratios - Khasanah, Nikmatul; van Noordwijk, Meine; Slingerland, Maja; Sofiyudin, Mohammad; Stomph, Dienke; Migeon, Adrien F.; Hairiah, Kurniatun (Frontiers in Sustainable Food Systems, 2020)
Driven by increased global demand for vegetable oil in the food and biofuel sectors, oil palm plantations based on monoculture technology have expanded into lowland tropical forests. Interest in diversified, mixed oil palm systems is increasing as these might increase efficiency of the use of land and other resources, reduce farmer risk, and decrease greenhouse gas (GHG) emissions per unit product. Land Equivalent Ratio for provisioning services (LERP) values above 1.0 show that at least some diversified systems use land more efficiently than monocultures and are thus “land sparing,” where monoculture LERP cannot exceed 1.0. Diversification also modifies climate and water regulating functions (“land sharing”) relative to a forest reference, as indicated in the LERR index. A “multifunctional” LERM indicator combines both; land sparing plus land sharing effects jointly determine expected regulating services. Empirical assessment of multiple ecosystem services in agricultural landscapes is assisted by models that synthesise process-based knowledge, especially for perennial systems where well-designed experiments require a full production cycle, and are costly and scarce. Agroforestry models explore spacing, intercropping and soil management options, predicting harvestable yields, impacts on water flows, nutrient leaching, and greenhouse gas emissions. We used the process-based Water, Nutrient and Light Capture in Agroforestry System (WaNuLCAS) model to explore mixed oil palm + cocoa and oil palm + pepper intercrop systems with modified (“double row”) planting patterns for Indonesian contexts and estimated consequences for the carbon footprint. The oil palm + cocoa intercrop provided a high LERP (1.4), while also replenishing more ground water and having a lower C footprint. This combination also has a return to labour equal to that in oil palm monocultures and a higher benefit cost ratio than the oil palm + pepper combination that maximizes Net Present Value. Oil palm + cocoa systems are also less sensitive to price uncertainty for oil palm, and buffer for oil palm and cocoa production risks, assumed to be independent of each other. Considerable economic and environmental system improvements appear to be feasible through mixed oil palm systems and diversification as a pathway to intensification deserves full attention of research and policy development.